THE EFFECT OF TREATMENT OF WATERBOLE JUICE ON BLOOD PRESSURE REDUCTION IN HYPERTENSION PATIENTS: LITERATURE REVIEW - Mashuri Mashuri; Rizeki Dwi Fibriansari; Indriana Noor Istiqomah; Risma Wahyu Khandidah (STIKes Kepanjen, 2022)
Hypertension is generally caused by an unfavorable lifestyle includingexcessive salt consumption because salt can increase blood pressure quicklyin some people, especially for people with severe hypertension, people withmild hypertension, and people with old age. This study aims to explain theeffect of giving watermelon juice on reducing blood pressure in patients withhypertension. The writing method used is a literature review related to theeffect of giving watermelon juice on reducing blood pressure in patients withhypertension. Journals used as references were obtained by Schoolar, andTaylor and Francis. The results showed that there was an effect of givingwatermelon juice on reducing blood pressure in patients with hypertension.Watermelon juice can also neutralize blood pressure so that watermelon juiceconsumers will not experience a continuous decrease in blood pressure. Sothat people with hypertension can consume regularly with a healthy lifestyle.